2018
DOI: 10.1136/bmjpo-2017-000245
|View full text |Cite
|
Sign up to set email alerts
|

Hypothermia for encephalopathy in low-income and middle-income countries: feasibility of whole-body cooling using a low-cost servo-controlled device

Abstract: Although therapeutic hypothermia (TH) is the standard of care for hypoxic ischaemic encephalopathy in high-income countries, the safety and efficacy of this therapy in low-income and middle-income countries (LMICs) is unknown. We aimed to describe the feasibility of TH using a low-cost servo-controlled cooling device and the short-term outcomes of the cooled babies in LMIC.DesignWe recruited babies with moderate or severe hypoxic ischaemic encephalopathy (aged <6 hours) admitted to public sector tertiary neona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
22
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 24 publications
1
22
2
Order By: Relevance
“…19,[41][42][43] Schultheiss et al concluded that hypothermia could protect retina ganglion cells against ischemia and increase the ischemic tolerance time for optic cells. 41 Moreover, research evidences show that hypothermia has a neuroprotective role for patients suffering from subarachnoid hemorrhages, 44 encephalopathy, 10 and cerebral edema due to stroke, 45 which supports this study results.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…19,[41][42][43] Schultheiss et al concluded that hypothermia could protect retina ganglion cells against ischemia and increase the ischemic tolerance time for optic cells. 41 Moreover, research evidences show that hypothermia has a neuroprotective role for patients suffering from subarachnoid hemorrhages, 44 encephalopathy, 10 and cerebral edema due to stroke, 45 which supports this study results.…”
Section: Discussionsupporting
confidence: 86%
“…3 Recently, among different modes of intervention, hypothermia has been recognized for improving the final outcome of the diseases. 10 Hypothermia was first introduced in cardiac patients after cardiopulmonary resuscitation (CPR) studies showed that hypothermia was very effective. 11,12 Researchers hypothesized that mild hypothermia after stroke could reduce the neurological damage and delay brain death.…”
Section: Introductionmentioning
confidence: 99%
“…Although the NICU applications improved, the overall prevalence of morbidity in children born with meconium stained amniotic fluid is still high 1,10 . This present study indicated for the first time the therapeutic effect of hypothermia on meconium induced lung injury in a newborn rat model.…”
Section: ■ Discussionmentioning
confidence: 99%
“…In some series, meconium stained liquor has been still reported in 22% to 55% of infants with hypoxic-ischemic encephalopathy (HIE) 10 . Therapeutic hypothermia has widely recommended in the standard of care for neonates with HIE 11 .…”
Section: ■ Introductionmentioning
confidence: 99%
“…Worldwide, the impact of brain cooling has dramatically reduced incidence of hypoxic-ischaemic encephalopathy; whilst low-and middle-income countries lag in this, costeffective devices are now being introduced through collaborative projects between neonatologists and child neurologists. 4 Research should be clinically applicable. Commencing with a clinical challenge and working backwards to the underlying cause is essential.…”
mentioning
confidence: 99%